Distinct interfacial ordering of liquid crystals observed by protein–lipid interactions that enabled the label-free sensing of cytoplasmic protein at the liquid crystal-aqueous interface. Issue 23 (4th November 2021) - Devi, Manisha; Verma, Indu; Pal, Santanu Kumar
Abstract : Different lipid laden liquid crystal-aqueous interfaces facilitate the imaging of the cytoplasmic protein JM-EGFR at nanomolar concentrations. Abstract : Interfaces formed between a lipid decorated liquid crystal (LC) film and an aqueous phase can mimic the bimolecular membrane where interfacially occurring biological phenomena ( e.g., lipid–protein interactions, protein adsorption) can be visually monitored by observing the surface-sensitive orientations of LCs. The ordering behavior of LCs at different phospholipid-based LC interfaces (1, 2-dilauroyl- sn-glycero -3-phosphocholine (DLPC) and lysophosphatidic acid (LPA)) were investigated to determine the sensing of an important cytoplasmic protein (juxtamembrane of epidermal growth factor receptor (JM-EGFR)). At both DLPC and LPA decorated interfaces, the LC adopts homeotropic ordering, causing a dark optical appearance under crossed polarizers. Interestingly, upon the introduction of JM-EGFR to these LC-aqueous interfaces, the homeotropic orientation of the LC changed to planar (bright optical appearance), suggesting the potential of the designed system for JM-EGFR sensing. The use of different lipid decorated LC-aqueous interfaces results in the emergence of distinct optical patterns. For example, at a DLPC laden interface, elongated bright domains are observed, whereas a uniform bright texture is observed on an LPA laden interface. The DLPC decorated LC-aqueous interface is found to be highly selective for the sensing of JM-EGFR with a detection limit in the nanomolar concentration region (∼ 50 nM). When compared to spectroscopic and other conventional techniques, the LC-based design is simpler, and it allows the simple and label-free optical sensing of JM-EGFR at fluidic interfaces.